The relationship between pain score and change in physiological indices of premature neonates under ventilation - Zahra Khalili; Mehdi Molavi Vardanjani; Saba Bashiri; Arash Khalili (Kurdistan University of Medical Sciences, 2018)
Background & Aim: Tracheal suctioning is one of the ways to clean and open the airway in infants admitted to the neonatal intensive care unit that can be with many negative consequences such as pain, decrease in arterial oxygen saturation, pneumonia, heart rhythm disorder, change In the rhythm and number of respiration and sepsis. Materials & Methods: This is a descriptive correlational study with IR.UMSHA.REC.1395.424 ethical code, was performed on 120 preterm infants in neonatal intensive care unit of Besat and Fatemieh Hospitals of Hamedan. Firstly, before suctioning the patient, the heart rate index of the newborn that needed to be suctioned was registered by the researcher in three shifts based on the findings of the direct monitoring of the infant. The heart rate index was re-recorded during suction. Data were analyzed using descriptive and regression tests. Results: Infants with a catheter of 6 to 9 french were suctioned at 80 to 85 suction pressure. In 26% of cases, the suctioning standards for the duration of suction, standard pressure and proper size of the catheter were not observed. There was a significant difference between the change in heart rate index and pain score (P=0.001). Conclusion: Failure to observe suction standards in premature infants can lead to changes in heart rate index and increase their basic needs, which can impair the recovery process of preterm infants.